2007
DOI: 10.1002/pros.20670
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of E‐cadherin and β‐Catenin proteins in metastatic prostate cancer cells in bone

Abstract: BACKGROUND. The expression of E-cadherin in the intercellular adhesion of metastatic prostate cancer cells in bone, which is the most prevalent site of metastatic growth, remains elusive. METHODS. The aim of the study was to compare the concurrent membranous expression of E-cadherin and b-catenin proteins, the state which is known to be associated with the cellular adhesion function of E-cadherin, in prostate biopsy tissue specimens by immunohistochemical staining method. The expression patterns of E-cadherin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 17 publications
2
73
0
2
Order By: Relevance
“…Six studies [45, 46, 4951, 53] investigated the differential expression of E-cadherin in PC bone metastases. Two of these reported lower expression of E-cadherin in bone metastasis tissues compared to matched primary PC tissues [46, 51].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [45, 46, 4951, 53] investigated the differential expression of E-cadherin in PC bone metastases. Two of these reported lower expression of E-cadherin in bone metastasis tissues compared to matched primary PC tissues [46, 51].…”
Section: Resultsmentioning
confidence: 99%
“…Tu et al (18) demonstrated that dysregulation of TGF-β signaling in prostate cancer plays a causal role in promoting tumor metastasis. Catenin, mediated by Wnt signaling, serves two cellular roles: the first in conjunction with T-cell factors (TCF) in the transcription control of proteins key to cell proliferation and the second as a part of a complex with E-cadherin, an extracellular binding matrix that promotes intercellular adhesion (19,20). Adherens junction is the process by which E-cadherin mediates cell adhesion in tissue required for morphological changes leading to changes in the phenotype (11,19,20).…”
Section: Resultsmentioning
confidence: 99%
“…Catenin, mediated by Wnt signaling, serves two cellular roles: the first in conjunction with T-cell factors (TCF) in the transcription control of proteins key to cell proliferation and the second as a part of a complex with E-cadherin, an extracellular binding matrix that promotes intercellular adhesion (19,20). Adherens junction is the process by which E-cadherin mediates cell adhesion in tissue required for morphological changes leading to changes in the phenotype (11,19,20). Lastly, tight junction mediates cell motility, and research [these mechanisms are reviewed in the study by Martin and Jiang (21)] shows a significant role for tight junctions in maintaining cell-to-cell integrity, such that perturbations can lead to invasion and metastasis of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Saha et al (27) reported that loss of e-cadherin gene expression is caused by reversible epigenetic mechanisms, and showed that e-cadherin gene expression was present in metastatic bone lesions of prostate carcinoma. it was hypothesized that e-cadherin gene expression might be the last fact to provide advantage tumor cells to make clusters in metastatic areas (26). these recent studies raise doubt on the suppressor role of e-cadherin on metastasis and invasion.…”
Section: Resultsmentioning
confidence: 99%